Eksplorasi Label Halal, Electronic Word of Mouth, dan Influencer Media Sosial terhadap Keputusan Pembelian dengan Citra Brand sebagai Variabel Intervening - Buanantari, Alfina; Arinta, Yusvita Nena (Journal of Halal Industry Studies, 2024)
This study aims to determine the effect of halal labels, electronic word of mouth, and social media influencers on purchasing decisions for Sariayu cosmetics with brand image as an intervening variable. The type of research used is quantitative research. The data collection method was carried out through questionnaires distributed to Sariayu cosmetics consumers in Boyolali Regency. The sample was taken from 96 respondents using a purposive random sampling technique. This study used path analysis to test the intervening variables. Based on the research test conducted, the results found that the variables halal labels, electronic word of mouth, and social media influencers significantly positively affect brand image. The variables halal labels and brand image have a significant positive effect on purchasing decisions, and the variables electronic word of mouth and social media influencers do not significantly affect purchasing decisions—the results of the Path test show that the halal label affects purchasing decisions mediated by brand image. In contrast, electronic word of mouth and social media influencers do not affect purchasing decisions mediated by brand image.